A method to estimate turbulence intensity and transverse Taylor microscale in turbulent flows from spatially averaged hot-wire data - Segalini, Antonio; Orlu, Ramis; Schlatter, Philipp; Alfredsson, P. Henrik; Rueedi, Jean-Daniel; Talamelli, Alessandro (Experiments in Fluids, 2011)
A new approach to evaluate turbulence intensity and transverse Taylor microscale in turbulent flows is presented. The method is based on a correction scheme that compensates for probe resolution effects and is applied by combining the response of two single hot-wire sensors with different wire lengths. Even though the technique, when compared to other correction schemes, requires two independent measurements, it provides, for the same data, an estimate of the spanwise Taylor microscale. The method is here applied to streamwise turbulence intensity distributions of turbulent boundary layer flows but it is applicable generally in any turbulent flow. The technique has been firstly validated against spatially averaged DNS data of a zero pressure-gradient turbulent boundary layer showing a good capacity to reconstruct the actual profiles and to predict a qualitatively correct and quantitatively agreeing transverse Taylor microscale over the entire height of the boundary layer. Finally, the proposed method has been applied to available higher Reynolds number data from recent boundary layer experiments where an estimation of the turbulence intensity and of the Taylor microscale has been performed. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2023-03-21